2017
DOI: 10.1371/journal.pone.0188098
|View full text |Cite
|
Sign up to set email alerts
|

A 17-molecule set as a predictor of complete response to neoadjuvant chemotherapy with docetaxel, cisplatin, and 5-fluorouracil in esophageal cancer

Abstract: BackgroundRecently, neoadjuvant chemotherapy with docetaxel/cisplatin/5-fluorouracil (NAC-DCF) was identified as a novel strong regimen with a high rate of pathological complete response (pCR) in advanced esophageal cancer in Japan. Predicting pCR will contribute to the therapeutic strategy and the prevention of surgical invasion. However, a predictor of pCR after NAC-DCF has not yet been developed. The aim of this study was to identify a novel predictor of pCR in locally advanced esophageal cancer treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…GSE93756, GSE94012, GSE104958, and GSE143822 datasets are selected from National Center for Biotechnology Information's (NCBI) Gene Expression Omnibus (GEO, https://www.ncbi.nlm.nih.gov/geo/) [16]. GSE93756 dataset has four samples based on platform [17]. GSE143822 dataset has eight samples, and it is based on platform GPL20844 Agilent-072363 SurePrint G3 Human GE v3 8x60K Microarray 039494.…”
Section: Methodsmentioning
confidence: 99%
“…GSE93756, GSE94012, GSE104958, and GSE143822 datasets are selected from National Center for Biotechnology Information's (NCBI) Gene Expression Omnibus (GEO, https://www.ncbi.nlm.nih.gov/geo/) [16]. GSE93756 dataset has four samples based on platform [17]. GSE143822 dataset has eight samples, and it is based on platform GPL20844 Agilent-072363 SurePrint G3 Human GE v3 8x60K Microarray 039494.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, PET-negative LNs after NAC were an independent prognostic factor in the univariate and multivariate analyses. We previously reported that some molecular biomarkers might be predictive factors for esophageal cancer in patients treated with NAC[ 28 ]. If these predictive molecular biomarkers can be clarified further, it is possible that patients with PET-negative LNs after NAC could avoid esophagectomy and undergo strict surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Others utilized cross-validation approaches in a single data set; this approach can be helpful if seeking to evaluate a marker combination, particularly where sample sizes are small [ 36 , 50 , 61 , 90 ]. Seven studies used independent data sets for validation [ 53–55 , 60 , 93 , 95 , 96 ]. Ultimately, the highest level of evidence of validity comes from using an independent sample set that is not used to generate the initial computational model and this is widely recommended [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Four studies examined mRNA biomarkers in OSCC alone and, similarly to OAC, they varied significantly [ 53–56 ]. Motoori et al .…”
Section: Predictive Biomarkers In Oesophageal Cancermentioning
confidence: 99%
See 1 more Smart Citation